Sexuality in the elderly: knowledge and attitudes of professional caregivers - Senra, Margarida (2014)
INTRODUCTION: Sexuality in the elderly still remains a taboo, especially in the institutional context. Demographic changes have been occurring these past few years which led to an increase in the number of institutionalized elders, as an attempt to respond their needs. OBJECTIVES: This study aims to know the levels of knowledge and attitudes of the professional caregivers, how these are related and how these relate with the socio demographic variables. METHODS: Quantitative, exploratory, comparative and correlational study. Convenience sample of professional caregivers (n=329), which accepted to participate by answering to the Aging Sexual Knowledge and Attitudes Scale (ASKAS), which allowed the knowledge and attitudes measure about sexuality in the elderly. RESULTS: There is a positive correlation between the knowledge levels and the attitudes and, generally, the caregivers present good knowledge levels and the attitudes about sexuality in the elderly are permissive. However, there is a difference between the qualified technicians and the auxiliary staff, as the former present better knowledge levels and more permissive attitudes. Generally, the individuals with higher educational qualifications also present higher knowledge levels and more permissive attitudes. None of subjects referred attending any kind of training or education in this area. Single individuals present better knowledge levels and more permissive attitudes than the married ones. The older individuals present less permissive attitudes as well as the more experienced caregivers. CONCLUSION: The knowledge is related with the attitudes about sexuality in the elderly. This topic remains a delicate subject for many of the individuals, especially for who work in an institutional context. Education and training of these caregivers and a continuous research play a key role in the quality of life of the elders and the quality of the provided services.